Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.
đề bài : -3/7- (2/3 - 3/7 )
= -3/7 - 5/21
= -2/3
b) 2/15 : ( 1/3 . 4/5 - 1/3 . 6/5 )
= 2/15 : ( 1/3 . 4/5 + 6/5 )
=2/15 : 1/6
=4 /5
bạn nhớ cho mình nha
a, -3/7 - { 2/3 - 3/7 }
= -3/7 - 2/3 + 3/7
= -3/7 + 3/7 - 2/3
= 0 - 2/3
= -2/3
b, 2/15 : [ 1/3 . 4/5 -1/3 . 6/5 ]
= 2/15 : [ 1/3 . ( 4/5 - 6/5 )]
= 2/15 : [ 1/3 . ( -2/5 )]
= 2/15 : ( -2/15 )
= -1
a)
\(\frac{-3}{7}-(\frac{2}{3}-\frac{3}{7})\)
=\(\frac{-3}{7}-\frac{5}{21}\)
=\(\frac{-2}{3}\)
b)
\(\frac{2}{15}:(\frac{1}{3}.\frac{4}{5}-\frac{1}{3}.\frac{6}{5})\)
=\(\frac{2}{15}:[\frac{1}{3}.(\frac{4}{5}-\frac{6}{5})]\)
=\(\frac{2}{15}:(\frac{1}{3}.\frac{-2}{5})\)
=\(\frac{2}{15}:\frac{-2}{15}\)
=-1